Evaluation of Type 2 Diabetes Mellitus Chronic Disease Management Policy to Improve Self-Care Management - Abubakar, Amira Bin Seh; Mallongi, Anwar; Muhammad, Alazhar; ., Muhlisa; Salewe, Wahyuni (Journal of Cultural Analysis and Social Change, 2025)
Type 2 Diabetes Mellitus (T2DM) is a global health problem that requires long-term and collaborative management. Self-care management is the main key in controlling this disease effectively. Chronic disease management policies in various countries have been widely implemented, but their effectiveness in improving self-care management still needs further study. This study aims to further examine the evaluation of chronic disease management policies for type 2 diabetes mellitus to improve self-care management. Literature review was conducted by searching and analyzing journals from the Pubmed and Schimago portals with predetermined inclusion and exclusion criteria. Key search terms were identified using truncated words (in this case *) with Type 2 Diabetes Mellitus" OR "T2DM" AND "chronic disease management" OR "policy evaluation" OR "health policy" AND "self-care management" OR "self-management" OR "patient engagement". Most studies indicate that policy-based interventions such as patient education programs, primary healthcare integration, and digital health support contribute positively to improving self-care management in T2DM patients. However, their effectiveness varies across regions and health systems. Comprehensive and integrated chronic disease management policies have been shown to be effective in improving self-care management in T2DM patients. These findings can serve as a reference in formulating more responsive health policies.